Effect of the foliage of Tagetes minutaon Meloidogyne incognitaroot-galling on Capsicum annuumin a greenhouse - Murga-Gutiérrez, Santos Nélida (2012)
The effect of the foliage of Tagetes minuta"huacatay" on Meloidogyne incognitaroot-galling on Capsicum annuum"paprika pepper" cultured in a greenhouse was researched, to obtain a control strategy for this nema-tode. Three experimental groups and one control with 12 pots each were used, which contained sterilized soil and sand (1:1). To this substrate was added cut foliage of T. minutaat 20, 35 and 50% (v/v) according to the experimental group, and the control group remained without this amendment. In each pot a seedling of C. annuum was sown, and one week post-seeding was inoculated with 5000 eggs of M. incognita. Eight weeks later the root galling was evaluated. All the plants had root galling; although the number of galls in plants of the experimental groups was less than those in the control group with statistical significant difference (p< 0.05). Among the numbers of galls in the plants of the three experimental groups there was no significant difference (p> 0.05). It is concluded that the foliage of T. minutaadded as organic amendment at 20, 35 and 50% to the culture soil for C. annuumplants limits the M. incognitaroot galling. That suggests its potential use in the control of this nematode.